AB0024 ASSOCIATION OF IL6 RS1800795 BUT NOT IL6R RS2228145, RS4845618 AND STAT4 RS7574865 POLYMORPHISMS WITH CHLAMYDIA-ASSOCIATED RHEUMATOID ARTHRITIS. (2nd June 2020) - Zybalova, T.; Yagur, V.; Goncharova, R.; Soroka, N.; Dostanko, N.; Apanasovich, V.; Tushina, A.
Abstract : Background: Rheumatoid arthritis (RA), associated with Chlamydial Infection, has some clinical and immunological particulars that interfere with the early diagnosis and require significant changes in treatment strategy [1]. Objectives: To estimate the distribution of some non-HLA genetic markers such as STAT4 rs7574865, IL6 rs1800795, IL6R rs2228145 and rs4845618 in Chlamydia positive and negative RA patients and healthy controls. Methods: We examined 380 healthy blood donors and 187 RA patients classified according to the ACR/EULAR 2010 criteria for RA [2]. Twenty-three of the RA patients were positive for Chlamidia trachomatis (n=17) or Chlamidia pneumonia (n=6) persistence. DNA from peripheral blood samples was extracted by phenol-chloroform method. SNPs were genotyped by the real-time PCR with fluorescent probes. Statistical significance of SNPs' frequency was estimated by two-way Fisher exact test (F, p2-t ) with Bonferroni correction for multiple comparisons (pcor ). Moreover, diagnostic odds ratio (dOR), the likelihood ratio of positive (LR + ) and negative (LR – ) tests and corresponding confidence intervals (CI) were calculated. Results: We revealed statistically significant increase of genotype СС frequency (IL6 rs1800795) in Chlamydia-associated RA (60.9%) vs healthy donors (20.7%): p2-t =0.000065; pcor =0.00026; dOR=5.95 (CI95% 2.53-13.94); LR + =2.94 (CI95% 1.90-3.29); LR – =0.49 (CI95% 0.28-0.75) as well as in Chlamydia-associated RA (60.9%) vs Chlamydia-negative RA (23.9%): p2-t =0.00051; pcor =0.002; dOR=4.99 (CI95% 2.04-12.16); LR + =2.56 (CI95% 1.60-3.57); LR – =0.51 (CI95% 0.29-0.78). Significant differences in STAT4 rs7574865, IL6R rs2228145 and IL6R rs4845618 distribution between studied groups were not found. Conclusion: Our data suggest the association between СС genotype of IL6 rs1800795 and Chlamydia-associated RA. References: [1]Soroka N.F. Rheumatoid Arthritis, associated with Chlamydial infection // Healthcare 2009; 1: 5-9. [2]Aletaha D. et al. 2010 Rheumatoid arthritis classification criteria// Arthritis Rheum 2010; 62 (9): 2569-81. Disclosure of Interests: Tatiana Zybalova: None declared, Viktor Yagur: None declared, Roza Goncharova: None declared, Nikolaj Soroka Grant/research support from: JSC BIOCAD, Natalia Dostanko: None declared, Valery Apanasovich: None declared, Anastasiya Tushina: None declared